Security Substrate Based Security Management and Control Mecbanism of Reconfigurable Network - Jie Chen; Jianwei Liu; Mengmeng Wang; Shuangyu He; Jian Mao (Dianxin kexue)
The next generation internet security architectures were analyzed and the characteristics and security challenges of the existing network were studied. The security goals of reconfigurable network were defined, and the“security substrate”based security management and control mechanism of reconfigurable network was presented. The definition of “security substrate”was given and the corresponding reconfigurable networks security model was illustrated. The construction of security services with multilevel security structure and security service establishment process via “security substrate”were put forward, which were key components of the security management and control architecture of reconfigurable network.